Integrate QTL Mapping and Transcription Profiles Reveal Candidate Genes Regulating Flowering Time in Brassica napus - Liu, Zigang; Dong, Xiaoyun; Zheng, Guoqiang; Xu, Chunmei; Wei, Jiaping; Cui, Junmei; Cao, Xiaodong; Li, Hui; Fang, Xinlin; Wang, Ying; Tian, Haiyan (Frontiers in Plant Science, 2022)
Flowering at the proper time is an important part of acclimation to the ambient environment and season, and maximizes plant yield. To reveal the genetic architecture and molecular regulation of flowering time in oilseed rape (Brassica napus), we performed RNA-seq analysis of the two parents after vernalization at low temperature and combined this with quantitative trait loci (QTL) mapping in an F2 population. A genetic linkage map that included 1,017 markers merged into 268 bins and covered 793.53 cM was constructed. Two QTLs associated with flowering time were detected in the F2 population. qFTA06 was the major QTL in the 7.06 Mb interval on chromosome A06, and accounted for 19.3% of the phenotypic variation. qFTC08 was located on chromosome C06, and accounted for 8.6% of the phenotypic variation. RNA-seq analysis revealed 4,626 differentially expressed genes (DEGs) between two parents during vernalization. Integration between QTL mapping and RNA-seq analysis revealed six candidate genes involved in the regulation of flowering time through the circadian clock/photoperiod, auxin and ABA hormone signal, and cold signal transduction and vernalization pathways. These results provide insights into the molecular genetic architecture of flowering time in B. napus.